2001
DOI: 10.2310/6650.2001.34047
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Glucocorticoids in Peripheral Blood Mononuclear Cells of Chronic Fatigue Syndrome Patients, without Evidence for Altered Density or Affinity of Glucocorticoid Receptors

Abstract: In conclusion, PBMC of CFS patients display an increased sensitivity to glucocorticoids, which cannot be explained by number or affinity of the GR but should rather be attributed to molecular processes beyond the actual binding of the ligand to the GR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In a later study, employing a whole blood assay with LPS-stimulation, they further showed an increased GC sensitivity of IL-10, but not IL-12 production (Visser et al, 2001a). These results were replicated in a further study, in which they additionally reported that the differences in GC sensitivity were not attributable to variation of GR expression or binding affinity (Visser et al, 2001b). Accordingly, Gaab et al…”
Section: Gc Sensitivity In Psychiatric and Somatic Diseasesmentioning
confidence: 82%
“…In a later study, employing a whole blood assay with LPS-stimulation, they further showed an increased GC sensitivity of IL-10, but not IL-12 production (Visser et al, 2001a). These results were replicated in a further study, in which they additionally reported that the differences in GC sensitivity were not attributable to variation of GR expression or binding affinity (Visser et al, 2001b). Accordingly, Gaab et al…”
Section: Gc Sensitivity In Psychiatric and Somatic Diseasesmentioning
confidence: 82%
“…Further sup port for enhanced negative feedback and increased glucocorticoid sensitivity came from three in vitro studies. [44][45][46] Three new in vivo studies published in the past 8 years have lent further support to the presence of enhanced negative feedback and glucocorticoid receptor func tion. The first study 47 applied the lowdose DST to 34 female patients, 12 of whom had a history of childhood trauma.…”
Section: Suppression Studiesmentioning
confidence: 87%
“…Visser and coworkers reported IL-10 to be increased (69) and normal (70), while another group reported it to be decreased (14).…”
Section: Inconsistent Levels Of Soluble Mediators Cytokines or Theimentioning
confidence: 99%
“…One group reported increases in IL-2 cytokine (58), while three groups found amounts of this cytokine to be at control levels (10,40,70).…”
Section: Inconsistent Levels Of Soluble Mediators Cytokines or Theimentioning
confidence: 99%